2021
DOI: 10.1016/j.anl.2020.06.014
|View full text |Cite
|
Sign up to set email alerts
|

The role of endoscopic resection for selected patients with sinonasal squamous cell carcinoma

Abstract: Despite of rapid advances in endoscopic surgery, the gold standard for sinonasal squamous cell carcinoma (SNSCC) surgery has remained the open approach with en-block resection due to the aggressive nature of SNSCC, including frequent recurrence and high mortality rate. For that reason, few studies have focused on SNSCC treated by endoscopic surgery alone. The objective of this study was to evaluate the usefulness of endoscopic surgery for patients with SNSCC. Methods: A retrospective analysis was performed for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 21 publications
0
31
0
Order By: Relevance
“…Regarding surgical margins, in the study by Nakamaru et al, 4 of the 15 patients (27%) showed positive surgical margins [21] . None of the patients with negative surgical margins ( n = 11) showed recurrence.…”
Section: Surgical Marginsmentioning
confidence: 93%
See 4 more Smart Citations
“…Regarding surgical margins, in the study by Nakamaru et al, 4 of the 15 patients (27%) showed positive surgical margins [21] . None of the patients with negative surgical margins ( n = 11) showed recurrence.…”
Section: Surgical Marginsmentioning
confidence: 93%
“…Nakamaru et al reported no postoperative complications among 15 consecutive SN-SCC patients who underwent exclusively EES [21] . Kılıc et al reported that hospital stay was significantly shorter in patients with SN-SCC treated with endoscopic resection (endoscopic: 2.50 days; open: 4.67 days; p < 0.0001) according to the National Cancer Database [35] .…”
Section: Surgical Complications Associated With Ees For Sn-sccmentioning
confidence: 96%
See 3 more Smart Citations